Changes in the microbiological and physico-chemical properties of chocolate paste processed into premium whole milk bars - Guerrero, Vicelle G.; Rillo, Belen O. (1989)
Samples of chocolate paste (raw materials) and Premium Whole Milk Bars (finished product) were subjected to microbiological and physico-chemical tests. The total plate count and yeast and mold count for both chocolate paste and Premium Whole Milk Bars exceeded the microbiological standard of Philippine Cocoa Corporation. Zero counts were obtained for the coliform count. Physic-chemical test results showed that the chocolate samples had an average pH value of 6.00, Aw value of 0.60, and %FFA of 0.3936. T-test results indicated no significant change in the microbial load and the physico-chemical properties of chocolate paste processed into chocolate bars. Premium Whole Milk Bars were divided into two lots and stored at different conditions - Ambient Condition (28-30°C, 81% RH) and Accelerated Condition (35-37°C), 100% RH). Computed correlation coefficient indicated that no relationship exist between the pH, Aw, %FFA properties and TPC and YMC of the samples stored. However, at accelerated condition a direct relationship between the Aw and the total plate count was obtained with a correlation coefficient of 73.6%. Changes in the physical attributes: appearance, color, and texture, of the stored samples were observed.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Chocolate processing